The design of radiology viewing box using light emitting diode and potentiometer - Diartama, Anak Agung Aris; Suswaty, Susy; Priantoro, Win; Sugiyanto, Sugiyanto; Sudiyono, Sudiyono; Anwar, M. Choiroel; Latifah, Leny; Santjaka, Aris; Amri, Faisal; Mulyantoro, Donny Kristanto (Global Health Management Journal, 2017)
Background: In the process of work to gain the maximum results, a radiologist needs a viewing box tool to read radiographs. Therefore, the authors want to develop a viewing box tool, which in general the work if this tool resembles the factory manufactured tool. The viewing tool box made can adjust the intensity of the light produced.Objective: to create a viewing box tool by using a potentiometer system.Methods: This study used applied research method by creating and using the design of viewing box tool by using a potentiometer system and testing the viewing box tool created by using a Lux meter and 15 respondents consisting of five radiologists and 10 radiographers who should fulfill the questionnaire form.Results: The mean of viewing box illumination reached 220 lux. The results of the questionnaire showed that 100% radiologist gave an A (excellent) and expressed that the viewing box tool created could be used properly and 90% radiographers provided an A (excellent) and expressed that the viewing box tool created could be used properly, while 10% radiographer gave a value of B (moderate).Conclusion: viewing box tool created could be used properly and obtained optimal results as a tool in reading radiographs. Potentiometer system contained in the viewing box was very helpful in reading radiographs because it allowed to adjust the light intensity according to user needs.Keywords       :  Viewing box, Potentiometer Bibliography   : 1980-2011